Foreign Competition and Domestic Innovation: Evidence from U.S. Patents - David Autor; David Dorn; Gordon H. Hanson; Gary Pisano; Pian Shu (Institute of Labor Economics (IZA), 2019)
Manufacturing accounts for more than three-quarters of U.S. corporate patents. The competitive shock to this sector emanating from China's economic ascent could in theory either augment or stifle U.S. innovation. Using three decades of U.S. patents matched to corporate owners, we quantify how foreign competition affects domestic innovation. Rising import exposure intensifies competitive pressure, reducing sales, profitability, and R&D expenditure at U.S. firms. Accounting for confounding sectoral patenting trends, we find that U.S. patent production declines in sectors facing greater import competition. This adverse effect is larger among initially less profitable and less capital-intensive firms.
Keywords: F14; O30; 330; innovation; patents; trade